Astronomia acessível no Município de Feira de Santana: um olhar voltado para a pessoa com deficiência visual - Santos, Ana Lúcia de Jesus dos Passos (2020)
In this research, we investigate the possibilities the accessible Astronomy for the people with visual impairments in the city of Feira de Santana located at Bahia´s state (Brazil). Our study was anchored in the historical-cultural perspective and in previous studies on actions to promote accessibility of Astronomy in Brazil and the world, for both formal and non-formal teaching spaces. As a methodology, we have adopted the qualitative one, in the research-action modality with direct insertion in the reality of the involved students. Our public was blind and with the low vision capabilities students as well as their teachers, totalizing 22 students and 15 teachers of the Center for the Visually Impaired in Feira de Santana. The research was based not only on the fieldwork that involved interviews for both students and teachers but also carrying out practical activities in order to establish relationships and building knowledge related to the Astronomy. The involvement of the students was very expressive, and they participated in the activities proposed as well as visited the Museu do Observatório Astronômico Antares/UEFS, which allow them to know not only the workflow of this Museum but also to how incorporated it is the accessibility. As the educational product, was elaborated a didactic manual composed by a didactic sequence to explore the concepts related to the Solar System with the students with visual impairments; a celestial dome using styrofoam material adapted to represent the Feira de Santana´s night sky as well as a memory game with Solar System components. This research aims to contribute for the development for the accessibilities proposals for the visual impairments community in Feira de Santana, in which there is only a few activities turned to this finality.